2016
DOI: 10.1016/j.resp.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory motor training and neuromuscular plasticity in patients with chronic obstructive pulmonary disease: A pilot study

Abstract: The objective of this study was to examine the feasibility of a full-scale investigation of the neurophysiological mechanisms of COPD-induced respiratory neuromuscular control deficits. Characterization of respiratory single- and multi-muscle activation patterns using surface electromyography (sEMG) were assessed along with functional measures at baseline and following 21 ± 2 (mean ± SD) sessions of respiratory motor training (RMT) performed during a one-month period in four patients with GOLD stage II or III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
2
10
0
5
Order By: Relevance
“…Previous studies suggested that respiratory motor training could induce functional improvements in patients with stable chronic COPD. [69] In addition, respiratory muscle endurance training increased breathing and cycling endurance in sedentary subjects. [10] Currently, in China, pursed lips breathing, abdominal breathing, and inspiratory muscle training [11] are widely used for patients with stable chronic COPD combined with general exercise training.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that respiratory motor training could induce functional improvements in patients with stable chronic COPD. [69] In addition, respiratory muscle endurance training increased breathing and cycling endurance in sedentary subjects. [10] Currently, in China, pursed lips breathing, abdominal breathing, and inspiratory muscle training [11] are widely used for patients with stable chronic COPD combined with general exercise training.…”
Section: Introductionmentioning
confidence: 99%
“…2 In hence, the respiratory muscles need adequate work to maintain effective sustaining respiration. 3 Some studies argue that respiratory muscle fatigue can impair exercise effectiveness. They demonstrate that the inspiratory muscle training (IMT) slows the respiratory muscle fatigue, lactate concentration and metaboreflex, which can increase the strength and respiratory muscle strength, thereby improving performance in thesport.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the QoL in patients affected by this disease, scientists have suggested different adjuvant to medical treatment, such as psychological (for anxiety and depression) and psychosocial support (Farver-Vestergaard et al, 2015 ), respiratory motor training (Ovechkin et al, 2016 ), physical activity (Araújo, 2016 ) mindfulness-based (Mularski et al, 2009 ), and educational interventions (Harris et al, 2008 ) also for healthcare professionals (Pelland et al, 2017 ). However, taken individually, these approaches have not always given satisfying results.…”
Section: Introductionmentioning
confidence: 99%